2017
DOI: 10.1248/bpb.b16-00853
|View full text |Cite
|
Sign up to set email alerts
|

Atractylenolide III Enhances Energy Metabolism by Increasing the SIRT-1 and PGC1α Expression with AMPK Phosphorylation in C2C12 Mouse Skeletal Muscle Cells

Abstract: Targeting energy expenditure provides a potential alternative strategy for achieving energy balance to combat obesity and the development of type 2 diabetes mellitus (T2DM). In the present study, we investigated whether atractylenolide III (AIII) regulates energy metabolism in skeletal muscle cells. Differentiated C2C12 myotubes were treated with AIII (10, 20, or 50 µM) or metformin (2.5 mM) for indicated times. The levels of glucose uptake, the expressions of key mitochondrial biogenesis-related factors and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 27 publications
4
20
0
Order By: Relevance
“…Interestingly, in the present study, ARA increased PGC1α and phosphorylated AMPK protein levels and the protein levels of NRF1 and TFAM, which are both downstream transcription factors of PGC1α [ 18 ]. Furthermore, these findings are consistent with those that we previously reported for C2C12 skeletal muscle cells [ 15 , 16 ]. In addition, PGC1α has been shown to regulate the expressions of endogenous antioxidant proteins [ 19 ], and, in the present study, we observed that ARA also increased levels of antioxidant enzymes, such as HO-1 and catalase.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Interestingly, in the present study, ARA increased PGC1α and phosphorylated AMPK protein levels and the protein levels of NRF1 and TFAM, which are both downstream transcription factors of PGC1α [ 18 ]. Furthermore, these findings are consistent with those that we previously reported for C2C12 skeletal muscle cells [ 15 , 16 ]. In addition, PGC1α has been shown to regulate the expressions of endogenous antioxidant proteins [ 19 ], and, in the present study, we observed that ARA also increased levels of antioxidant enzymes, such as HO-1 and catalase.…”
Section: Discussionsupporting
confidence: 93%
“…ARA or fermented ARA have been reported to reduce body weights and serum lipid levels in high fat diet (HFD) induced animal models of obesity [ 13 , 14 ], but the mechanisms responsible for these anti-obesity effects have not been elucidated. In a previous study, we found ARA increased lipid and glucose metabolism by enhancing the activities of peroxisome proliferator-activated receptor gamma coactivator 1 alpha (PGC1α) and adenosine monophosphate-activated protein kinase (AMPK) in C2C12 skeletal muscle cells [ 15 ], and, in a following study, we showed that atractylenolide III (the primary bioactive component in ARA) also enhanced PGC1α and AMPK activities in C2C12 cells [ 16 ]. However, no reports have been previously issued on the regulation of energy metabolism by ARA in an obese animal model.…”
Section: Introductionmentioning
confidence: 99%
“…Oral administration of Ang-(1-7) and resveratrol improved metabolic profile through a cross-modulation between RAS and sirtuins [76]. The correlation between sirtuins and AMPK was also be reported in the experiments [153,154]. Many studies have shown the important role of sirtuins in the relationship between RAS and AMPK which we have already mentioned before [76,85,109,112].…”
Section: Sirtuinsmentioning
confidence: 57%
“…There are twelve activated regulators of various categories, with three transcription regulators (IRF3, ZBTB20, PPARGC1A), a cytokine (IFNB1), a transporter (SFTPA1), two drugs (stallimycin, bromodeoxyuridine), as listed in Table 2 . For instance, the protein encoded by PPARGC1A (PPARG coactivator 1 alpha) is known to bind and regulate many genes involved in energy metabolism[ 20 ]. It interacts with PPARγ and PPARα, which in turn mediate interactions with multiple transcription factors[ 21 ].…”
Section: Resultsmentioning
confidence: 99%